Factors affecting sustainable urbanization among five ASIAN highly industrialized countries (Hong Kong, Singapore, South Korea, Japan, China) - Khiew, Yin Wei; Tan, Suet Ping; Teh, Min Yee (2024)
This research aims to investigate the factors that influence sustainable urbanization in highly industrialized and developed Asian countries such as Hong Kong, Singapore, South Korea, Japan, and China. In addition, this study examined the relationship between the dependent variable which is sustainable urbanization, and each factor influencing sustainable urbanization in highly industrialized Asian countries. The factors include the economic development level, education level, industry structure, and institutional quality. This research uses annual data for the independent variables from a sample of five developed Asian countries from 2010 to 2019. The data used in this study are secondary data with a total of 50 observations. Based on the panel data, we subsequently utilized Pooled Ordinary Least Squares (OLS), Fixed Effect Model (FEM), and Random Effect Model (REM) to analyze the significance of the factors that influence sustainable urbanization. Using the Hausman Test, Redundant Fixed Effect, and Breusch-Pegan Lagrange Multiplier Test (LM), the most effective estimated model was chosen. The diagnostic checking for autocorrelation, heteroscedasticity, and multicollinearity are also conducted in order to identify any economic issues underlying the model.